2010
DOI: 10.4049/jimmunol.0903631
|View full text |Cite
|
Sign up to set email alerts
|

Highly Pathogenic Influenza Virus Infection of the Thymus Interferes with T Lymphocyte Development

Abstract: Highly pathogenic avian influenza viruses (HPAIVs) cause severe disease in humans. Still, the basis for their increased pathogenesis remains unclear. Additionally, the high morbidity in the younger population stays inexplicable, and the recent pandemic H1N1v outbreak in 2009 demonstrated the urgent need for a better understanding about influenza virus infection. In the present study, we demonstrated that HPAIV infection of mice not only led to lung destruction but also to functional damage of the thymus. Moreo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
48
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 46 publications
3
48
1
Order By: Relevance
“…Apoptosis of thymic T-cells (especially DP T-cells) has been reported to be the main cause of thymic atrophy (Liu et al, 2014;Savino, 2006;Vogel et al, 2010). In our study, in addition to DP T-cell apoptosis we found that influenza virus infection significantly suppressed the proliferation of thymic T-cells (especially DN T-cells), as shown by the obvious decrease in BrdU incorporation (Fig.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Apoptosis of thymic T-cells (especially DP T-cells) has been reported to be the main cause of thymic atrophy (Liu et al, 2014;Savino, 2006;Vogel et al, 2010). In our study, in addition to DP T-cell apoptosis we found that influenza virus infection significantly suppressed the proliferation of thymic T-cells (especially DN T-cells), as shown by the obvious decrease in BrdU incorporation (Fig.…”
Section: Discussionsupporting
confidence: 61%
“…This discrepancy might be caused by differences in the infecting virus dose, virulence and mouse strains. Vogel et al (2010) showed that highly pathogenic IAV could infect the thymus and interfere with T-cell development. Liu et al (2014) showed that elevated IFN-c produced by innate CD8…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphopenia can result from impaired development or destruction of lymphocytes. Vogel et al reported that H5N1 virus infection in mice led to massive lung damage and infection of respiratory DCs, and proposed that the migration of infected DCs into the thymus interferes with T lymphocyte selection processes (29). We show that lethal highly pathogenic avian influenza (HPAI) H5N1 influenza virus infection results in increased destruction of lymphocytes by up-regulation of FasL expression on pDCs and that FasL+ pDCs are responsible for apoptosis of influenza-specific CD8 + T cells.…”
Section: Introductionmentioning
confidence: 99%
“…Comment on "Highly Pathogenic Influenza Virus Infection of the Thymus Interferes with T Lymphocyte Development" I read with much interest the article by Vogel et al (1), who state that the cause for lymphopenia in severe infections has been hitherto unclear and, based on their findings, propose that highly pathogenic infectious agents such as influenza virus directly impede the development of lymphocytes, and hence account for lymphopenia. However, the authors have overlooked a well-studied and very important mechanism for lymphopenia, one involving glucocorticoids, which have been used as chemotherapeutic agents against hematological malignancies for decades.…”
mentioning
confidence: 94%